INKULTURASI IMAN KRISTEN DALAM BUDAYA TORAJA: TELAAH TEOLOGIS TERHADAP PRAKTIK RAMBU SOLO' DAN PEMAKNAANNYA DALAM TERANG INJIL - Merianti Rama Karuru; Noviani Kalutte', Elvaisa Padudung, Arni Palantia, Meli Krisma Dei (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This article discusses the efforts of inculturation of Christian faith in Torajan culture, especially through the practice of traditional funeral rituals known as Rambu Solo’. Inculturation is understood as a process of encounter between the Gospel and local culture that takes place critically and dialogically, with the aim of presenting a faith that is contextual but remains faithful to the truth of the Bible. Rambu Solo’ as a death rite contains not only customary aspects, but also rich theological symbolism in the Torajan people's understanding of life, death, and respect for ancestors. Through a literature study method, this study examines the symbolic meaning of Rambu Solo’, identifies the theological challenges that arise, and explores opportunities for evangelism through the development of contextual liturgy and faith education. The results of the study indicate that the church has a strategic role in directing the inculturation process through pastoral care, culturally sensitive theological education, and open dialogue with the community. This article recommends the need for a deep understanding of local culture so that the Christian faith can be fully experienced in the lives of the people without losing its theological integrity. Healthy inculturation allows the gospel to truly be grounded, giving new meaning to cultural symbols, and strengthening the church's witness in a multicultural society like Toraja